Ecological-social-economic analysis of urban climate governance based on climate plans and reports of Ukraine's cities of regional significance - Vitaliy Soloviy; Ion Dubovich (Наукові праці Лісівничої академії наук України, 2020)
Ukraine is facing accelerating climate change, yet national climate policy doesn’t live up to the urgency of climate challenges. In times when state-driven climate action fails to deliver, cities emerge as hotspots of vulnerability and islands of hope for preserving a liveable climate. In this article, we conduct a critical interdisciplinary analysis of how 78 large Ukrainian cities that are signatories to the Global Covenant of Mayors for Climate & Energy perform on their climate commitments and governance, as well as on the sustainability paradigms they adhere to. As a theoretical lens of the study we employ the classification of urban sustainability paradigms: weak, strong, critical and transformative. We view those paradigms across three analytical levels of (philosophical-ethical, theoretical-methodological and empirical), using this as a qualitative reference for further analysis. Within each paradigm, we provide a review of key concepts and approaches that relate to and reflect each of the paradigms. Our analysis suggests that most cities fall into the weak sustainability paradigm and adhere to approaches and tools that are not fit to the unique challenges of climate change. All of the presently available plans are built upon standard theory and methods of neoclassical economics. Thus, they do not manage to recognize the uniqueness of climate change. Most of them lack legitimacy and are insufficiently ambitious in their intended contribution to the Paris targets while approaching the planning process in a purely formalistic fashion. They seldom achieve defined goals and prioritize overly narrow range of technical measures without considering prospective co-benefits of other options, do not conduct any meaningful actions for adaptation and provide fragmented reports, which allow judging on progress made only in select cases. A number of positive trends should however be noted, such as the emergence of niche innovations, the development of collaborative networks and accumulation of mitigation experience in particular sectors. We develop a new analytical tool to assess the effectiveness of urban climate governance based on city plans, reporting and data. It includes three groups criteria (analysis, organizational capacity and implementation) and ten sub-criteria (awareness, vulnerability, inventory, vision and goals, coordination, participation resourcefulness, achievements, reporting and evaluation, and communication). Consistently applying those criteria allows to holistically grasp and assess the effectiveness of the present governance system throughout all its phases. The article concludes with suggestions on moving beyond the current status quo of weak sustainability and towards a strong sustainability paradigm through a set of strategic, operational and tactical measures, including coverage of such aspects as: updating climate change narratives; extending state support to urban climate action; extending capacities of scientists and decision-makers considering the unique challenges of the Anthropocene; assessing both consumption and production-based emissions; updating decision-making criteria to effectively integrate a wide range of co-benefits of climate action; advancing research on nature-based climate solutions and the role of civil society; greater consideration of interconnections between climate targets and sustainability goals; consideration of various stakeholder perspectives, including vulnerable groups and others who are often left excluded from such processes. At the present moment it is important to invest in institutional capacity building and social learning, build effective cross-level collaborations, seek support from international financial institutions and guidance from the transnational municipal climate networks.